Producción de Enterotoxina y Biofilm en Aislamientos Clínicos de Staphylococcus aureus Resistente a Meticilina - Ávila R Yeiny; Ginestre P Messaria; Valero L Kutchynskaya; Castellano G Maribel; Romero A Sonia; López Alfredo; Rincón V Gresleida; Sandrea T Lisette (Universidad del Zulia,Facultad de Medicina,Departamento de Enfermedades Infecciosas y Tropicales, 2014)
Abstract: S. aureus has become a public health problem, due to the difficulty of treating infections caused by methicillin-resistant S. aureus (MRSA). The purpose of this research was to determine the production of enterotoxins A, B, C and D and the production of biofilm in clinical isolates of MRSA. Fifty MRSA strains isolated from different types of clinical samples were studied. Detection of enterotoxins was carried out using the technique of reversed phase agglutination, while biofilm production was studied through two tests: Congo red agar and the microplate cell culture method. Enterotoxin production was observed in 9 strains (18%); enterotoxin D (64%) was the most prevalent, followed by B (27%) and A (9%). A significant association was shown between enterotoxin production capacity and the type of sample that came from the strain. Biofilm production was found in 30% and 98% of the strains using the Congo red Agar and microplate cell culture methods, respectively. A correlation of both trials was observed in only 15 strains (30%). It was shown that the microplate cell culture method is more effective for detecting biofilm production in S. aureus strains. Resumen: S. aureus se ha convertido en un problema de salud pública, debido a la dificultad que representa el tratamiento de las infecciones causadas por SARM. El propósito de esta investigación fue determinar la producción de enterotoxinas A, B, C y D y la producción de biofilm en aislamientos de SARM. Se estudiaron 50 cepas aisladas de diferentes tipos de muestras clínicas. La detección de enterotoxinas se realizó por la técnica de aglutinación en fase reversa y la producción de biofilm mediante: agar rojo congo y el método en microplacas de cultivos celulares. La producción de enterotoxina se observó en 9 cepas (18%), siendo la enterotoxina D (64%) la más prevalente, seguida de la B (27%) y la A (9%). Se demostró una asociación significativa entre la producción de enterotoxina y el tipo de muestra de la que provenía la cepa. La producción de biofilm se ...